A systematic literature review on the translator's voice - Guo, Xiaohui; Ang, Lay Hoon; Xie, Chaoqun (Sciedu Press, 2023)
The translator’s voice, although ubiquitous in translation, is not clearly determined when it is applied to translation practices because translator’s voice and translation practices are not conceptually connected. This systematic review focuses on the body of literature regarding the translator’s voice. In this study, academic articles from 1996 to 2023 are surveyed by a criteria pre-set; in addition, a qualitative synthesis of the findings is conducted. Through description and analysis of the titles, abstracts, keywords, and full papers of the selected 50 academic articles based on a PRISMA flow (2020), this research systematically assesses the studies on translator’s voice from the past 27 years. It systematically searched all the related studies in two databases: the China National Knowledge Infrastructure (CNKI) and Scopus (which are both accessible). It reveals: (1) more conceptual studies, more of which are unrelated to translation practices, are found; and (2) topics related to narratology are the most studied research objectives of the entire body of the studies covering the translator’s voice. Therefore, empirical studies and the translator’s voice in translated texts which are close related to translation techniques can both be highlighted in future research efforts. Future studies relating the translator’s voice to translation practices are needed so that translator’s voice can clearly present a translator’s creativity.